To the fauna of gastrointestinal nematodes of sheep in the European part of Russia - I. A. Pimenov; D. N. Kuznetsov; I. M. Odoevskaya; A. D. Afanasyev; A. I. Varlamova; I. A. Arkhipov (Российский паразитологический журнал, 2023)
The purpose of the research is to study the fauna of gastrointestinal nematodes of sheep in the European part of the Russian Federation.Materials and methods. The studies were carried out in 2022–2023. The objects for the study were the sets of the gastrointestinal tracts of sheep aged from one to 2.5 years, delivered to the slaughterhouse in the Moscow region from different regions of the Russian Federation, including the Oryol and the Astrakhan regions, the Republic of Dagestan and Stavropol Krai. After slaughter, 10 sets of gastrointestinal tracts were taken by the random sampling method from each batch of delivered sheep. Then, these sets of gastrointestinal tracts were subjected to helminthological necropsy according to the method of K. I. Skryabin (1928). The species of detected nematodes were identified according to K. I. Skryabin et al. (1952) and V. M. Ivashkin et al. (1989).Results and discussion. A different degree of gastrointestinal nematodes infection of sheep has been established in different regions of the European part of the Russian Federation. Thus, the rate of infection in the Oryol region was 80%, in the Astrakhan region – 100%, in the Republic of Dagestan – 100% and in Stavropol Krai – 50%. Sheep were infected with Trichostrongylus colubriformis and Teladorsagia circumcincta with an intensity of infection, on average, 251.86±25.2 and 99.25±9.9 ex./head respectively in the Oryol region; T. colubriformis (242.65±24.3 ex./head), T. circumcincta (76.6±7.7 ex./head.), Haemonchus contortus (6.5±0.7 ex./head) and Marshallagia marshalli (19±1.9 ex./head) in the Astrakhan region; T. colubriformis (89.7±9 ex./head), T. circumcincta (43.6±4.4 ex./head), H. contortus (6.8±0.7 ex./head) and M. marshalli (17.8±1.8 ex./head) in the Republic of Dagestan; T. colubriformis (20.2±2 ex./head) and T. circumcincta (11±1.1 ex./head) in Stavropol Krai. Thus, T. colubriformis and T. circumcincta were the most frequently found nematodes in sheep in all of the four studied regions, and these two species also showed the highest rates of infection. The noted low species diversity of nematodes is obviously associated with the mandatory use of anthelmintic drugs. The studied sheep were treated against parasites (according to the accompanying veterinary documentation). At the same time, the detection of nematodes in treated animals possibly indicates the presence of resistant strains.